Assessment of Knowledge Sharing among Undergraduate Students in Ambrose Alli University, Ekpoma, Nigeria - Aiyebelehin, James Afebuameh (MiddleBelt Journal of Library and Information Science, 2016)
With the increasing emphasis on collaborative work in organizations today, universities around the world have been structuring their curriculum to engage students in collaborative learning. Most universities in Nigeria have not paid attention to this aspect of learning. This study therefore investigated knowledge sharing among undergraduates in Ambrose Alli University. A descriptive survey research design was adopted and questionnaire and interview were used for data collection. The sample for the study was drawn from the population through multi-stage sampling whereby three (3) faculties were randomly selected and thereafter a total sample size of 250 students was drawn using random sampling techniques. A total of 222 copies of questionnaires were retrieved and analyzed using tables, percentages and frequency counts. The study found that the major sources of knowledge include the course instructors, the internet and classmates as indicated by 100%, 95% and 82% of the respondents, respectively. Learning from others, as indicated by 93.6% of respondents, was a major motivation for knowledge sharing. Furthermore, 85.5% of respondents feel it is important to share knowledge with other students for the benefit of all, even as Telephone (97.7%) and Online chat (91.4%) topped the preferred channels for sharing knowledge. Knowledge sharing among undergraduates is an aspect of knowledge management that needs to be encouraged to stimulate increased excellent academic performance among students in the 21st century. To this end, it was recommended that lecturers should give more group assignments to students to create an atmosphere for knowledge sharing